The role of emotions in higher education and group dynamics - Anna Tsiboukli; Thomas Babalis (1st International Conferece of the Network of Teaching and Learning Centers in Greece, 2023)
The role of emotions in higher education is recently recognised as significant for quality teaching and students’ learning (Mendzheritskaya & Hansen, 2019). Emotions affect the learning climate and outcomes, attendance rates and the quality of classroom relationships and interplays. However, emotions are often overlooked in tertiary education. On the contrary, in primary education they have received significant attention and in Adult Education they have been recognized as an important driving learning force (Tennant, 2019). Nonetheless, emotions and often negative emotions, prevail in higher education and concern the relationships that develop within the classroom setting where transference and countertransference are also present. Emotions, concern both, university teachers and students. This paper suggests that group dynamics can be employed to alleviate negative emotions and support sharing of knowledge and experience in a facilitating environment. Furthermore, reducing dropout rates is another challenge. However, the question remains to what extent this is possible to happen in large audiences and classrooms where facilities for group learning are not provided in most higher education institutions in Greece.